The segregated town in mid-century southern fiction - Lennon, Gavan (2016)
This thesis examines how southern novelists at mid-century used the fictional small town to critique racial segregation. Depictions of segregated towns across a selection of representative fictions share a typology of people and institutions – what I term offices – that combine to make these towns seem integral and functioning. In the segregated southern town, the community is contaminated by segregation and the paradoxes it engenders are revealed through the typology I uncover and explore in this thesis.